2022
DOI: 10.3389/fpsyg.2022.740925
|View full text |Cite
|
Sign up to set email alerts
|

Not the Master of Your Volitional Mind? The Roles of the Right Medial Prefrontal Cortex and Personality Traits in Unconscious Introjections Versus Self-Chosen Goals

Abstract: Humans are unconditionally confronted with social expectations and norms, up to a degree that they, or some of them, have a hard time recognizing what they actually want. This renders them susceptible for introjection, that is, to unwittingly or “unconsciously” mistake social expectations for self-chosen goals. Such introjections compromise an individual’s autonomy and mental health and have been shown to be more prevalent in individuals with rumination tendencies and low emotional self-awareness. In this brai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The findings in the study help add to existing explanations for the content and process of life goals and aspirations in the pursuit of health and well-being among emerging adults as outlined in Figure 1. The examination of decision-making in Self-Determination Theory is novel, but preliminary findings from a recent study highlight the important role that decision-making can play in goals and aspirations using a brain imaging approach (Quirin et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The findings in the study help add to existing explanations for the content and process of life goals and aspirations in the pursuit of health and well-being among emerging adults as outlined in Figure 1. The examination of decision-making in Self-Determination Theory is novel, but preliminary findings from a recent study highlight the important role that decision-making can play in goals and aspirations using a brain imaging approach (Quirin et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The process of pain acceptance can be assumed to be impaired when the intensity of stress or negative affect exceeds a critical threshold and access to extension memory (i.e., self-access) is inhibited (62,83). When access to self-referential knowledge networks is hampered, individuals tend to mistake imposed duties or expectations of others for self-chosen goals, even though they do not match their own preferences-a phenomenon referred to as self-infiltration (116)(117)(118).…”
Section: Flexible Goal Management and Pain Acceptancementioning
confidence: 99%
“…Right cortex stimulation via contralateral hand contraction led to lower rates of self-infiltration in the self-discrimination task (see, for example, Kuhl & Kazén, 1994), as measured by the number of low attractive goals assigned by the experimenter but confused in memory as self-selected as compared to a baseline measure. A recent pilot study using functional magnetic resonance imaging (fMRI) explored potential brain sources of this effect in 17 participants (Quirin et al, 2020). Specifically, applying the same paradigm as Baumann, Kuhl, and Kazén (2005), we found that representations of self-selected goals activated the left ventromedial prefrontal cortex (PFC), whereas representations of imposed goals activated the right ventromedial PFC, and that the amount of activity within the right ventromedial PFC cluster was inversely related to self-infiltration rates, suggesting that the right ventromedial PFC contributes to buffering alienation.…”
Section: History Of Duality Of Mind and Self-awareness In Philosophy ...mentioning
confidence: 99%